Spinal Anesthesia for Removal of Thoraco-Lumbar Pedicle Screw - Gyawali, Nirmal Kumar (Europasian Journal of Medical Sciences, 2019)
Background: Spinal anesthesia compared to the general anesthesia has advantages of decreased blood loss, better cardiovascular stability, and postoperative pain control. This study was designed to evaluate pedicle screw removal at the lateral position under spinal anesthesia. Methods: It is a prospective study done in patients with ASA (American Society of Anaesthesiologist) I and II with ages between 17 to 75 years of both sex admitted for pedicle screw removal surgery during the period March 2018 to April 2019 AD in Western Hospital and research center Nepalgunj. All patients were informed about the risk of conversion to general anesthesia in detail. Spinal anesthesia was given to all 83 patients who came for pedicle screw removal. Result: Out of all patients 54% were from Hills and the remaining 46% were from Terai. The commonest cause of injury was fall from a tree which was in 48 (57.8%) out of 83 cases. The commonest level of injury was L1 followed by L2. The operation was completed under spinal anesthesia. None of the patients required conversion to general anesthesia. And 69 (83.1%) patients did not require any additional medications whereas the remaining 14 (16.86%) needed additional medications. Conclusion: Spinal anesthesia is the safe and effective anesthetic technique for short duration spinal surgery eg pedicle screw removal in terms of perioperative events and in prolonged postoperative analgesia, as well as in terms of patient and surgeon’s satisfaction.